The Indonesian Government's Inconsistency in Handling the Covid-19 Pandemic - Radjab, Syamsuddin; Fuady, Muhammad Ikram Nur (Yuridika, 2021)
A clear legal framework is the basis of an effective policy, including when dealing with the Covid-19 pandemic. However, inconsistencies in this legal framework lead to legal uncertainty and public confusion. This research aims to critique the Indonesian government's approach to dealing with the Covid-19 pandemic, which began in early 2020, particularly the legal framework's inconsistency in enforcing different and ineffective legal sanctions at the central government and local government level. Normative research methods are used together with a statutory approach, while the research results are explained in a descriptive-qualitative way. This research shows that the government considers the Covid-19 pandemic a non-natural disaster and does not implement lockdowns. Meanwhile, the legal framework used is the health quarantine law, which requires implementing responses to public health emergencies very similar to lockdowns. In addition, the Large-Scale Social Restriction (PSBB) policy has its legal basis in a health quarantine law, while the Covid-19 pandemic situation is considered a non-natural disaster subject to the disaster management law. Furthermore, other results also show ineffective enforcement of legal sanctions, such as criminal sanctions in regional head decisions that cannot be enforced because the PSBB policy only includes administrative sanctions. In conclusion, the inconsistency of the legal framework in dealing with the Covid-19 pandemic is very detrimental to the community due to its impact on human rights, which can lead to legal uncertainty and public distrust of the government.